Satisfaction with justice and desire for revenge in survivors of the September 11, 2001, attacks on New York City's World Trade Center. (1st October 2020) - Zettl, Rachel E.; Page, Lindsay E.; Bhatti, Saira; Duong, Karen; Patel, Tulsie; Dykema, John R.; Whitney, Meagan; Ayvaci, Emine R.; North, Carol S.; Sonis, Jeffrey
ABSTRACT: This study investigated gaps in existing knowledge on justice, desire for revenge, and associated factors in disaster research through data collected nearly three years post disaster on justice and revenge from survivors of the September 11, 2001 (9/11) attacks. A volunteer sample of 379 employees of eight affected businesses completed interviews and self-report questionnaires. Individual ratings on satisfaction with justice and desire for revenge were compared with demographic characteristics, disaster-related experience, posttraumatic stress disorder (PTSD), disaster-related distress, anger, and concerns about danger and safety. High levels of desire for revenge and relatively low levels of satisfaction with accountability for perpetrators of the 9/11 attacks were endorsed. Most of the associations between the justice scores and the revenge score with the disaster response variables were directionally consistent. Dissatisfaction with perpetrator accountability was associated with greater desire for revenge. Both of these variables were associated with greater concerns about danger and endorsement of security regulations at the expense of personal freedoms.